Strategi Sales Promotion D’pom Coffee Café Melalui Media Sosial Instagram - Muhamad Afrizal; Satya Indra Karsa (Bandung Conference Series: Communication Management, 2023)
Abstract. The rise of the phenomenon of consuming coffee for people in Indonesia has increased the number of requests from consumers for various kinds of unique brands. Competition in implementing sales promotion strategies in an effort to increase sales stimulus penetrates social media, especially Instagram. One of the D'Pom Coffee Cafés is implementing a sales promotion strategy through Instagram social media. In this study, researchers tried to analyze and describe in detail the sales promotion strategy used by D'Pom Coffee Café through Instagram social media @dpomcoffeekrw and the reasons for choosing this social media. This study uses qualitative methods, using a qualitative descriptive approach. This research will refer to the information provided by the informant who is one of the D'pom Coffee Café staff in the social media marketing section. Field data is in the form of the Instagram account page @dpomcoffeekrw. Data collection techniques used in this study were observation, interviews, and literature study. The results of this study show that D'Pom Coffe Café uses two marketing strategy concepts described by Haque-Fawzi, namely: the concept of market envy strategy and the concept of timing. The reason why D'Pom Coffee Café chose Instagram as a media in implementing sales promotion strategies concluded that the reach of the media is wide, Instagram users intersect with D'Pom Coffee Café's target consumers and the popularity of Instagram media as a marketing medium. Abstrak. Maraknya fenomena mengkonsumsi kopi bagi penduduk di Indonesia menaikkan angka permintaan dari pada kalangan konsumen akan berbagai macam brand yang unik. Persaingan dalam penerapan strategi sales promotion dalam upaya meningkatkan stimulus penjualan merambah kepada media sosial khususnya Instagram. D’Pom Coffee Café salah satunya ikut menerapkan strategi sales promotion melalui media sosial Instagram. Dalam penelitian ini, peneliti mencoba menganalisis dan mendeskripsikan secara detil strategi sales promotion yang digunakan D’Pom Coffee Café melalui media sosial Instagram @dpomcoffeekrw dan alasan dalam memilih media sosial tersebut. Penelitian ini menggunakan metode kualitatif, dengan menggunakan pendekatan deskriptif kualitatif. Penelitian ini akan mengacu kepada informasi yang diberikan oleh narasumber yang merupakan salah satu staff D’pom Coffee Café pada bagian social media marketing. Data lapangan berupa laman akun Instagram @dpomcoffeekrw. Teknik pengumpulan data yang digunakan dalampenelitian ini adalah observasi, wawancara, dan studi pustaka. Hasil penelitian ini diketahui bahwa D’Pom Coffe Café menggunakan dua konsep strategi pemasaran yang dijabarkan oleh Haque-Fawzi yaitu: Konsep Market Envy Strategy dan Konsep Timing. Adapun alasan D’Pom Coffee Café memilih Instagram sebagai media dalam penerapan strategi sales promotion disimpulkan bahwa daya jangkauan media yang luas, pengguna Instagram yang beririsan dengan target konsumen D'Pom Coffee Café dan kepopuleran media Instagram sebagai media pemasaran.